2023
DOI: 10.1002/clc.24033
|View full text |Cite
|
Sign up to set email alerts
|

The added value of hypertonic saline solution to furosemide monotherapy in patients with acute decompensated heart failure: A meta‐analysis and trial sequential analysis

Abstract: We assessed the effects of hypertonic saline solution (HSS) plus furosemide versus furosemide alone in patients with acute decompensated heart failure (ADHF). We searched four electronic databases for randomized controlled trials (RCTs) until June 30, 2022. The quality of evidence (QoE) was assessed using the GRADE approach. All meta‐analyses were performed using a random‐effects model. A trial sequential analysis (TSA) was also conducted for intermediate and biomarker outcomes. Ten RCTs involving 3013 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Several other studies and/or meta-analyses with hypertonic saline have reported similar results. [88][89][90][91][92] Conversely, the OSPREY-AHF (Oral Sodium to Preserve Renal Efficiency in Acute Heart Failure) trial, conducted in acute congested HF cases requiring intravenous diuretics, reported that adding up to 6 g of oral NaCl per day on top of liberal Na + and fluid intake, compared to placebo, did not result in a significant difference in the combined endpoint of weight change and creatinine change at 96 h or discharge. 85 In conclusion, based upon the current studies, there is no convincing evidence for a clear benefit of the addition of hypertonic saline during the treatment of acute decompensated HF.…”
Section: Acute Heart Failurementioning
confidence: 99%
“…Several other studies and/or meta-analyses with hypertonic saline have reported similar results. [88][89][90][91][92] Conversely, the OSPREY-AHF (Oral Sodium to Preserve Renal Efficiency in Acute Heart Failure) trial, conducted in acute congested HF cases requiring intravenous diuretics, reported that adding up to 6 g of oral NaCl per day on top of liberal Na + and fluid intake, compared to placebo, did not result in a significant difference in the combined endpoint of weight change and creatinine change at 96 h or discharge. 85 In conclusion, based upon the current studies, there is no convincing evidence for a clear benefit of the addition of hypertonic saline during the treatment of acute decompensated HF.…”
Section: Acute Heart Failurementioning
confidence: 99%